Basic social economy entities and social and economic benefits resulting from their activity - Janowski, Marcin (Ekonomia i Prawo. Economics and Law, 2020)
Motivation: Social economy has been playing increasingly important role in the EU member states regional development overcoming the phenomena included in the widely understood social and economic exclusion and degradation of natural environment. It so happens because social entrepreneurship bridges the gap resulting from ineffective and imposed actions of the third participant of economic process, namely the government trying to overcome the effects of above mentioned negative phenomena. The social entrepreneurship is becoming more and more important because of the local and regional character of activities, addressed directly to endangered social groups and geographic areas, solving problems at their source. In the European Union nearly 11 million people are employed in the sector of social economy and the number has been growing for many years. Therefore, it seems important to make the topic of social entrepreneurship and its impact on regional development the subject of scientific studies. In recent years, more attention is paid to various concepts, fulfilling not only economic, but also social and environmental goals; one of them undoubtedly includes social economy. Aim: This article aims at analysing specific form of entrepreneurship, namely social economy enterprises (PES), and presenting benefits resulting from their activity for regional development. The research methods applied in this study include inter alia the critical analysis of literature as well as evaluation and comparison of secondary research results from various sources. The scope of research refers to selected regions in Poland. The character of research work is illustrative. Results: The article indicates how the concept of social economy helps to eliminate the negative effects of social and economic exclusion. Through actions at the regional level, it is the social economy that acquires particular importance in voluntary, bottom-up solving of local community problems and supporting governmental activities. The results of the research of source materials presented in the article indicate that the level of development of social economy in different regions of Poland is of a varied nature, which may mean that its potential is not yet noticed everywhere.